Financial Performance Analysis at KSP Balo' Toraja Batutumonga Branch - Yohanis Lotong Tadung; Dwibin Kannapadang (Institute of Computer Science (IOCS), 2022)
Financial performance is a description of the company's financial condition in a certain period reflecting the health level of the company. This study aims to analyze the financial performance of the KSP Balo' Toraja cooperative. KSP Balo` Toraja is a company engaged in finance, especially those related to savings and loans. This research uses quantitative research. The procedure for collecting data in this study is documentation, namely by collecting available data from objects, especially financial report data in the form of research on KSP Balo' Tora j Batutumonga branch. The type of data used in this study is secondary data, namely the data obtained in the form of documents from KSP Balo' Tora j Batutumonga branch which includes balance sheets. The data analysis technique that will be used in this research is the Liquidity Ratio, Solvency Ratio which is used for the development of management performance in a period. From the results of the general analysis based on financial ratios, namely the liquidity position is already in an unhealthy condition because it has not optimized the use of assets so that current assets are idle, so that it is over liquid due to too many current assets. For the solvency ratio, it can be seen that it has increased. In the calculation DAR and DER indicate a healthy state. This is because KSP Balo' Toraja Batutumonga branch has been effective in managing finances.Financial performance is a description of the company's financial condition in a certain period reflecting the health level of the company. This study aims to analyze the financial performance of the KSP Balo' Toraja cooperative. KSP Balo` Toraja is a company engaged in finance, especially those related to savings and loans. This research uses quantitative research. The procedure for collecting data in this study is documentation, namely by collecting available data from objects, especially financial report data in the form of research on KSP Balo' Tora j Batutumonga branch. The type of data used in this study is secondary data, namely the data obtained in the form of documents from KSP Balo' Tora j Batutumonga branch which includes balance sheets. The data analysis technique that will be used in this research is the Liquidity Ratio, Solvency Ratio which is used for the development of management performance in a period. From the results of the general analysis based on financial ratios, namely the liquidity position is already in an unhealthy condition because it has not optimized the use of assets so that current assets are idle, so that it is over liquid due to too many current assets. For the solvency ratio, it can be seen that it has increased. In the calculation DAR and DER indicate a healthy state. This is because KSP Balo' Toraja Batutumonga branch has been effective in managing finances.